Suspected COVID-19 flu-like syndrome in men who have sex with men and have been involved in casual sex - Carvalho, Herica Emilia Félix de (2021)
OBJECTIVE: To evaluate the presence of flu-like syndrome suggestive of COVID-19 in men who have sex with men (MSM) and engaged in casual sex during a period of social isolation. METHOD: National epidemiological survey, applied in April and May 2020, by adaptation of Respondent Drive Sampling. RESULTS: 1,337 MSM participated in the survey, of which 514 (38.4%) had fever associated with another sign or symptom of flu-like syndrome. Social, demographic characteristics, sexual practices and activities during the period of social isolation were statistically associated with the presence of flu-like syndrome. There was a statistical difference (p < 0.001) in the average of partners between those who had signs and symptoms of flu-like syndrome (3.5) and those who did not (1.7). CONCLUSION: Evidence of signs and symptoms indicative of flu-like syndrome suggestive of COVID 19 in Brazilian MSM who were involved in casual sex during the period of social isolation. Objetivo: Evaluar la presencia de síndrome gripal sospecha de COVID-19 en hombres que tienen sexo con hombres (HSH) y se envolvieron en sexo con pareja ocasional durante distanciamiento social. Método:  Averiguación epidemiológica, de abarcamiento nacional, aplicado en abril y mayo de 2020, por adaptación delRespondent Drive Sampling. Resultados:  1.337 HSHs participaron de la investigación, de los cuales 514 (38,4%) tuvieron fiebre relacionada a otra señal o síntoma de síndrome gripal. Características sociales, demográficas, prácticas y actividades sexuales durante el distanciamiento social han estáticamente relacionadas a la presencia de síndrome gripal. Hubo diferencia estadística (p < 0,001) en la media de parejas entre aquellos que tuvieron señales y síntomas de síndrome gripal (3,5) y aquellos que no los tuvieron (1,7). Conclusión:  Se evidencia ocurrencia de señales y síntomas indicativos de síndrome gripal sugestivo de COVID-19 en HSHs brasileños que se envolvieron en sexo ocasional durante el período del distanciamiento social. Objetivo:  Avaliar a presença de síndrome gripal suspeita de COVID-19 em homens que fazem sexo com homens (HSH) e se envolveram em sexo com parceiro casual durante período de distanciamento social. Método:  Inquérito epidemiológico, de abrangência nacional, aplicado em abril e maio de 2020, por adaptação doRespondent Drive Sampling. Resultados:  1.337 HSHs participaram da pesquisa, dos quais 514 (38,4%) tiveram febre associada a outro sinal ou sintoma de síndrome gripal. Características sociais, demográficas, práticas e atividades sexuais durante o período de distanciamento social foram estaticamente associadas à presença de síndrome gripal. Houve diferença estatística (p < 0,001) na média de parceiros entre aqueles que tiveram sinais e sintomas de síndrome gripal (3,5) e aqueles que não os tiveram (1,7). Conclusão: Evidencia-se ocorrência de sinais e sintomas indicativos de síndrome gripal sugestiva de COVID19 em HSHs brasileiros que se envolveram em sexo casual durante o período do distanciamento social.